ОMMАVIY АХBОRОT VОSITАLАRI MEDIАSАVОDХОNLIK KОMPETENSIYАLАRINISHAKLLANTIRISH ОB’EKTI SIFАTIDА (Scientific journal of the Fergana State University, 2023)
This article presents the most convenient methods for the development of media competence of students of pedagogical higher educational institutions, justifies the development of academic disciplines in the learning process by means of information technology and multimedia technologies. According to the authors, special courses aimed at increasing the level of media competence, the possibility of deeper and more perfect assimilation of the transmitted material, an even greater desire for close contact with new areas of education, as a result of reducing the time for training, the possibility of saving time, the possibility of long-term storage of acquired knowledge in human memory and applying them in practice as necessary they allow graduates not only to get higher education, but also to receive education in an educational institution, the advantages of media competence over demonstrating a high level of media competence were analyzed using information from primary sources and scientific literature.